Nylon Membrane-Immobilized PCR for Detection of Bovine Viruses - Kenji Onodera; Jean d'Offay; Ulrich Melcher (BioTechniques)
Bridge TechnologyTM is an amplification technique in which pairs of primers are immobilized on a solid support, allowing amplification only at the location of the primer pair spot. The technique has diagnostic potential since an array of primer pairs, each specific for a different pathogen, can be used with a diagnostic sample without inter—pair interactions that plague the development of multiplex PCRs. As a result, one assay should be able to determine which of multiple pathogens are present and which are absent in each sample. As test material, we examined the specificity of detection of the RNA-containing bovine viral diarrhea virus (BVDV) and two DNA-containing bovine herpesviruses 1 and 2 (BHV-1 and BHV-2). Nylon membranes with two spots of UV-immobilized primer pairs–one for BVDV and one for BHV—were used in amplification with both corresponding templates, with each template singly and with no template. When amplification was assayed by chemiluminescent detection of incorporated DIG-nucleotides, the expected amplification patterns were obtained.